2023
DOI: 10.1101/2023.04.29.538716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic fidelity in complex biological systems and implications for ageing

Abstract: The study of age is plagued by a lack of delineation between the causes and effects within the ageing phenotype. This has made it difficult to fully explain the biological ageing process from first principles with a single definition. Lacking a clear description of the underlying root cause of biological age confounds clarity in this critical field. In this paper, we demonstrate that the epigenetic system has a built-in, unavoidable fidelity limitation and consequently demonstrate that there is a distinct clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Reducing such random variation by tightening regulatory mechanisms such as methylation maintenance and gene expression would be predicted to slow the aging process and could provide targetable approaches. This is therefore consistent with the epigenetic maintenance system (EMS) theory 25 , or the recently proposed information fidelity theory of aging 92 .…”
Section: Discussionsupporting
confidence: 87%
“…Reducing such random variation by tightening regulatory mechanisms such as methylation maintenance and gene expression would be predicted to slow the aging process and could provide targetable approaches. This is therefore consistent with the epigenetic maintenance system (EMS) theory 25 , or the recently proposed information fidelity theory of aging 92 .…”
Section: Discussionsupporting
confidence: 87%
“…We also show that the increase in entropy is driven by the differential shifts that trend from high and low methylation fractions in young, to intermediate methylation states at older ages; also referred to as the ‘smoothening of the epigenetic landscape,’ however, intermediately methylated CpGs that drift away from the mean towards fully methylated and unmethylated states decrease entropy, exhibiting ‘antientropic’ properties. It has been proposed that ‘anti-entropic’ CpGs could represent genes that become increasingly regulated 6 , a theory worth investigating further. Since the majority of DMPs are entropic, the net global effect is an increase in entropy with age.…”
Section: Discussionmentioning
confidence: 99%
“…Entropy can summarise all the age-related changes in DNAm using a single value, for a sample at a particular age, making it a highly useful in capturing the entirety of the age-related changes in the methylome. Previous literature has shown that DMPs shifting towards a methylation fraction of 50% drive entropy 4,5 , but there are also subsets of DMPs that trend away from the mean and may oppose or counteract the effect 6 .…”
Section: Introductionmentioning
confidence: 96%